The Effect of Leadership Style, Workload, and Work Environment on Employee Performance with Performance Assessment Moderation - Dayan Hakim Natigor Sipahutar; Rahmat Hidayatullah; Datep Purwa Saputra; Musa Alkadhim Alhabshy (International Journal of Business, Management and Economics, 2026)
Employee performance is a key factor in achieving success and organizational goals. Improving employee performance is an ongoing effort that requires a deep understanding of the factors influencing motivation, competence, and human resource development. Performance appraisal is the process of evaluating how well employees perform their jobs based on established standards. The study was conducted at Bank BJB Syariah's Jakarta Branch Office and Bekasi Consolidation Branch Office, and the study period was September 2025. The study population was all 145 organic employees working at Bank BJB Syariah's Jakarta Branch Office and Bekasi Consolidation Branch Office. The sample size was determined using the Slovin formula (Uma Sekaran, 2006), yielding a sample of 123 employees. The study concluded that leadership style had a positive and significant effect on employee performance, that workload had a negative and significant effect on employee performance, and that the work environment had a positive and significant effect on employee performance. Meanwhile, regarding the moderating influence, it is concluded that Performance Appraisal positively and significantly moderates the influence of Leadership Style on Employee Performance, Workload on Employee Performance, and Work Environment on Employee Performance.